2022
DOI: 10.1371/journal.pone.0272867
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA-C alleles and COVID-19 severity in a pilot study with a Spanish Mediterranean Caucasian cohort

Abstract: The clinical presentations of COVID-19 may range from an asymptomatic or mild infection to a critical or fatal disease. Several host factors such as elderly age, male gender, and previous comorbidities seem to be involved in the most severe outcomes, but also an impaired immune response that causes a hyperinflammatory state but is unable to clear the infection. In order to get further understanding about this impaired immune response, we aimed to determine the association of specific HLA alleles with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Additionally, the association of HLA‐C*04:01 was described in another previous study but, in this case, only in advanced age 39 . Additionally, Vigon et al found an association between HLA‐C alleles classified as C2, such as HLA‐C*0401 , especially in homozygosis, and disease severity, probably due to its lower capacity to present viral peptides in a stable form 35 . Although other studies did not found any association, 6,40,41 the sample size of SCOURGE supports the possibility of a firm association of these HLA class I alleles in the evolution of COVID‐19.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Additionally, the association of HLA‐C*04:01 was described in another previous study but, in this case, only in advanced age 39 . Additionally, Vigon et al found an association between HLA‐C alleles classified as C2, such as HLA‐C*0401 , especially in homozygosis, and disease severity, probably due to its lower capacity to present viral peptides in a stable form 35 . Although other studies did not found any association, 6,40,41 the sample size of SCOURGE supports the possibility of a firm association of these HLA class I alleles in the evolution of COVID‐19.…”
Section: Discussionmentioning
confidence: 46%
“…39 Additionally, Vigon et al found an association between HLA-C alleles classified as C2, such as HLA-C*0401, especially in homozygosis, and disease severity, probably due to its lower capacity to present viral peptides in a stable form. 35 Although other studies did not found any association, 6,40,41 the sample size of SCOURGE supports the possibility of a firm association of these HLA class I alleles in the evolution of COVID-19. One study published recently showed a strong association of HLA-B*15:01 with asymptomatic disease, 42 but this was not the case in our study.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The standard positive threshold that is empirically adopted for positive results is more than 5% CD63+ basophils [ 152 , 153 ]. The BAT can also be considered positive if a two-fold increase in the stimulation index (SI) is observed.…”
Section: Etiologic Diagnosis: Identification Of the Culprit Drugmentioning
confidence: 99%